Sistem Pendukung Keputusan Pemilihan Supplier Obat Terbaik Dengan Menggunakan Metode Promethee - Annisak Izzaty Jamhur (Smart Education, 2022)
The development of information technology has brought many changes in almost all fields. Every company changes to follow every technology development. Data collection methods used are observation, literature study, interviews. The analysis carried out includes analysis of the current system and analysis of the proposed system. The results of this system test conclude that creating a decision support system can help the pharmacy parties involved to facilitate the selection of the best drug supplier.